2022
DOI: 10.2196/36577
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effectiveness of Blended Cognitive Behavioral Therapy Compared With Face-to-Face Cognitive Behavioral Therapy for Adult Depression: Randomized Controlled Noninferiority Trial

Abstract: Background Internet-based cognitive behavioral therapy (iCBT) has been demonstrated to be cost- and clinically effective. There is a need, however, for increased therapist contact for some patient groups. Combining iCBT with traditional face-to-face (FtF) consultations in a blended format may produce a new treatment format (B-CBT) with multiple benefits from both traditional CBT and iCBT, such as individual adaptation, lower costs than traditional therapy, wide geographical and temporal availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Our findings are in line with previous studies on blended treatment for depression and anxiety, suggesting comparable clinical effects between the blended and control intervention (Kooistra et al, 2019;Ly et al, 2015;Mathiasen et al, 2022;Nakao et al, 2018;Romijn et al, 2021b;Thase et al, 2018). Results from Berger et al (2018) and Zwerenz et al (2017) indicated moderate between-group effect sizes in favor of blended, but these studies offered the online component as an adjunctive tool to usual care rather than an integrated blended treatment protocol as replacement of usual psychotherapeutic care.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are in line with previous studies on blended treatment for depression and anxiety, suggesting comparable clinical effects between the blended and control intervention (Kooistra et al, 2019;Ly et al, 2015;Mathiasen et al, 2022;Nakao et al, 2018;Romijn et al, 2021b;Thase et al, 2018). Results from Berger et al (2018) and Zwerenz et al (2017) indicated moderate between-group effect sizes in favor of blended, but these studies offered the online component as an adjunctive tool to usual care rather than an integrated blended treatment protocol as replacement of usual psychotherapeutic care.…”
Section: Discussionsupporting
confidence: 90%
“…Results from Berger et al (2018) and Zwerenz et al (2017) indicated moderate between-group effect sizes in favor of blended, but these studies offered the online component as an adjunctive tool to usual care rather than an integrated blended treatment protocol as replacement of usual psychotherapeutic care. Furthermore, trials are not fully comparable regarding the treatments that were received in the comparison groups, consisting of either standard CBT (Kooistra et al, 2019;Ly et al, 2015;Mathiasen et al, 2022;Thase et al, 2018), usual treatment with a psychotherapist (Berger et al, 2018) or psychiatrists (Nakao et al, 2018), or TAU with access to an online platform (Zwerenz et al, 2017). This makes direct comparisons of between-group effect sizes difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This theme included maximum oxygen consumption, comparison of bad cholesterol with good cholesterol, pain, diastolic blood pressure, systolic blood pressure, hypoglycemia, lipids, overall blood pressure, average blood sugar over last 3 months, physical function, fasting blood glucose, cholesterol, and BMI. There were 17% (16/92) of instances of increased mental health [ 31 , 32 , 37 , 39 , 43 , 45 , 47 , 54 , 57 ]. This theme encompassed anxiety, well-being, stress, loneliness, depression, fear, personal satisfaction, helplessness, rumination, acceptance, suicidal ideation, and resilience.…”
Section: Resultsmentioning
confidence: 99%
“…This theme encompassed anxiety, well-being, stress, loneliness, depression, fear, personal satisfaction, helplessness, rumination, acceptance, suicidal ideation, and resilience. There were 13% (12/92) of instances of improved medical engagement [ 28 , 30 , 32 , 35 , 36 , 40 , 43 , 46 , 48 , 60 ]. This theme included medication compliance, program or treatment adherence, follow-up visits, medical knowledge, and decrease in emergency department visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation